Evaluation of thermal performance factor by hybrid nanofluid and twisted tape inserts in heat exchanger - Noor Fouad. A. Hamza; Sattar Aljabair (Heliyon, 2022)
The thermal performance parameters of an improved heat exchanger tube fitted with various vortex generator inserts were investigated using numerical and experimental methods. The governing equations have been solved numerically by a Finite Volume approach employing the turbulence model (κ−ε). Two twisted tape types, which being inserted across a circular pipe (plain twisted tape) and (Double V-cut twisted tape), have been achieved. The hybrid nanofluid is prepared by using metal oxide [Al2O3+CuO] with distilled water at volume fraction range (0.6%, 1.2% and 1.8%), Reynolds number range (3560–8320) at twisted ratio (9.25). The experimental data for a plain tube, plain twisted tapes and double v-cut twisted tape are validated using the standard correlations available in the literature. The effect of such variables upon the average Nusselt number, friction factor, and thermal performance factor have been investigated and compared with a plain tube at the same conditions. As compared to plain twisted tape, the tube equipped with a double V-cut twisted tape with hybrid nanofluid displayed increased thermal performance. The greater vortex flow induced by the V-cuts results in more active thermal boundary layer disturbance, resulting in a greater heat transfer rate. The results show that thermal performance factor for hybrid nanofluid in plain circular tube at (∅=1.8%) and Reynolds number (8320) is about (1.068), when the plain twisted tape and double v-cut twisted tape inserted with hybrid nanofluid the thermal performance factor increased to (1.33) and (1.37), respectively. The results show a similar trend for both numerical and experimental cases. The comparison between the experimental and numerical results have maximum error was (9.7)%.